Synthesis Of Zinc Nanoparticles From Aqueous Extract Of Suaeda Monoica Salt Marsh Plant And Their Anti-Inflammatory Activities. - S.Bhavesh; Dr. Marina; Dr. Sivaperumal (Journal for ReAttach Therapy and Developmental Diversities, 2022)
Background: Aim: To study the anti inflammatory activity of zinc nanoparticles synthesized from extract of Suaeda monoica plant. Introduction: Suaeda monoica is a species of flowering plant in thr sea-blite genus Suaeda, largely native to the shores of the Indian ocean from South africa to Sri lanka. Zinc oxide nanoparticles are nanoparticles of zinc oxide that have diameters less than 100 nanometers. They have a large surfac area relative to their size and high catalytic activity. Material and methods: Collection of Suaeda monoica plant, preparation of aqueous extract from the plant by adding distilled water. 10 gm of plant added in 50 ml of distilled water, kept in shaker, then synthesis of nanoparticles from the extract. Results: The results showed positive results and had a good anti inflammatory activity at 100ul concentration of the sample, The proteinase inhibitor percentage was 40% and the absorbance of the sample was 260nm. Conclusion: The study showed that the anti inflammatory activity was good shown at 100ul concentration of the sample.